Efficacy and Safety of Neoadjuvant Intensity-Modulated Radiotherapy With Concurrent Capecitabine for Locally Advanced Rectal Cancer. Issue 2 (February 2015) - Wang, Lin; Li, Zi-Yu; Li, Zhong-Wu; Li, Yong-Heng; Sun, Ying-Shi; Ji, Jia-Fu; Gu, Jin; Cai, Yong
<x xml:space="preserve">Abstract</x> BACKGROUND: We previously conducted a prospective phase II clinical trial studying a unique 22-fraction neoadjuvant intensity-modulated radiotherapy with concurrent capecitabine treatment followed by total mesorectal excision for locally advanced rectal cancer. OBJECTIVE: The objective of this study was to retrospectively review the efficacy, toxicity, and surgical complications following intensity-modulated radiotherapy in patients who have rectal cancer. DESIGN: This was a retrospective study. SETTING: Data were gathered from a surgical database. PATIENTS: This study included patients who underwent intensity-modulated radiotherapy with gross tumor volume/clinical target volume of 50.6/41.8 Gy in 22 fractions with concurrent capecitabine treatment over a period of 30 days, after which the patients underwent surgery for rectal cancer in Peking University Cancer Hospital (2007–2013). MAIN OUTCOME MEASURES: The primary end points were acute toxicity, postoperative complications, and complete response rate. RESULTS: A total of 260 patients were included in our analysis. The median age was 55 years (range, 21–87 years), and 68.5% of the patients were male. The yield complete response rate was 18.5% (48/260). There were no grade 4 toxicity and perioperative mortality. The grade 3 toxicity rate was 5.8%, which included diarrhea (4.2%), neutropenia (1.2%), and radiation dermatitis (0.4%). The 30-day postoperative and severe complication (≥grade 3) rates were 23.1% and 2.7%. The anastomotic leakage rate was 3.3% (5/152). Perineal wound complications (29.2%, 28/96) represented the most common problem following abdominoperineal resection. The estimated 3-year local recurrence-free survival, cancer-specific survival, and disease-free survival rates were 94.2% (95% CI, 90.1%–98.3%), 92.2% (95% CI, 87.5%–97.0%), and 81.4% (95% CI, 75.4%–87.4%). LIMITATION: The retrospective nature and the single-arm design was the limitation of the study. CONCLUSION: The 22-fraction neoadjuvant intensity-modulated radiotherapy regimen used to treat rectal cancer in this study has a high efficacy rate and a low toxicity rate. Further studies are needed to better define the role of intensity-modulated radiotherapy for rectal cancer treatment in a neoadjuvant setting.